Synergistic photobiomodulation with 808-nm and 1064-nm lasers to reduce the β-amyloid neurotoxicity in the in vitro Alzheimer's disease models - Zhang, Renlong; Zhou, Ting; Samanta, Soham; Luo, Ziyi; Li, Shaowei; Xu, Hao; Qu, Junle (Frontiers in Neuroimaging, 2022)
Background In Alzheimer's disease (AD), the deposition of β-amyloid (Aβ) plaques is closely associated with the neuronal apoptosis and activation of microglia, which may result in the functional impairment of neurons through pro-inflammation and over-pruning of the neurons. Photobiomodulation (PBM) is a non-invasive therapeutic approach without any conspicuous side effect, which has shown promising attributes in the treatment of chronic brain diseases such as AD by reducing the Aβ burden. However, neither the optimal parameters for PBM treatment nor its exact role in modulating the microglial functions/activities has been conclusively established yet. Methods An inflammatory stimulation model of Alzheimer's disease (AD) was set up by activating microglia and neuroblastoma with fibrosis β-amyloid (fAβ) in a transwell insert system. SH-SY5Y neuroblastoma cells and BV2 microglial cells were irradiated with the 808- and 1,064-nm lasers, respectively (a power density of 50 mW/cm2 and a dose of 10 J/cm2) to study the PBM activity. The amount of labeled fAβ phagocytosed by microglia was considered to assess the microglial phagocytosis. A PBM-induced neuroprotective study was conducted with the AD model under different laser parameters to realize the optimal condition. Microglial phenotype, microglial secretions of the pro-inflammatory and anti-inflammatory factors, and the intracellular Ca2+ levels in microglia were studied in detail to understand the structural and functional changes occurring in the microglial cells of AD model upon PBM treatment. Conclusion A synergistic PBM effect (with the 808- and 1,064-nm lasers) effectively inhibited the fAβ-induced neurotoxicity of neuroblastoma by promoting the viability of neuroblastoma and regulating the intracellular Ca2+ levels of microglia. Moreover, the downregulation of Ca2+ led to microglial polarization with an M2 phenotype, which promotes the fAβ phagocytosis, and resulted in the upregulated expression of anti-inflammatory factors and downregulated expression of inflammatory factors.